Motivation and Self - Confidence and their relation to Routine Performance on Parallel Bars in Men's Artistic Performance - Mohammed Hamza; Jamal Sekran; Ahmed Abdullah Lafta (College of Physical Education and Sport Sciences, 2021)
The research aimed at identifying the relationship between motivation and self-confidence on the performing routines in the parallel bar. The researchers used the descriptive method on (480) thirds year college of physical education and sport sciences/ university of Baghdad students. The data was collected and treated using proper statistical operations to conclude that there is a high correlation relationship between motivation and self-confidence with routine performance on parallel bars. In addition to that, the researchers concluded that third-year students have high motivation and self - confidence and there is a positive relationship between motivation, self-confidence, and routine performance on parallel bars.